Modified emulsion polyvinyl chloride membranes for enhanced antifouling and dye separation properties by introducing tungsten disulfide (WS2) nanosheets - Aqaei, Houriye; Irani-nezhad, Mahsa Haddad; Khataee, Alireza; Vatanpour, Vahid (Elsevier, 2023)
In this study, the fabrication and modification of emulsion polyvinyl chloride (EPVC) membranes were studied using tungsten disulfide (WS2) nanosheets. The layered WS2 nanosheets were synthesized, characterized, and applied in the modification of EPVC membranes. The nonsolvent induced phase inversion method was utilized to fabricate new membranes by introducing the WS2 nanosheets into the polymeric solutions with different percentages. The performance of the fabricated membranes was characterized and evaluated using scanning electron microscopy, atomic force microscopy, attenuated total reflection-Fourier transform infrared, mean pore radius, porosity, contact angle analyses, pure water flux, fouling parameters, rejection tests for bovine serum albumin (BSA) and two dyes, and long-term and reusability tests. The results indicated that the use of WS2 nanosheets in the membrane structure up to the optimum value (1 wt%) increased the water flux and improved the antifouling properties. The pure water flux enhanced from 56.4 L/m2.h in the bare membrane to 191.2 L/m2.h in the 1 wt% WS2/EPVC membrane. In addition, the flux recovery ratio parameter increased from 64.7% to 83.5%. dye rejection rates of 94.7% and 97.8% were obtained for Reactive Red 195 and Reactive Green 19, respectively. Reusability tests for the 1 wt% WS2/ EPVC membrane indicated a slight flux drop and negligible BSA rejection changes. Long-term tests showed very high stability in dye rejection and a negligible flux drop.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Mixed matrix membranes; Polyvinyl chloride; Antifouling; Textile wastewater treatment